Design, simulation and experimentation of an electro-dynamic system for semi-active control of vibrations. Issue 1 (December 2020) - Popescu, N; Comeagă, C D; Avram, M
Abstract: Previous work regarding the vibration transmissibility control, using electrodynamic actuators, based on semi-active solutions, proved the efficiency of this strategy. The studied system is a simple, one degree of freedom system. The system integrates mechanical components for passive isolation and an electrodynamic actuator for active and semi-active control of vibrations. The most efficient solution is to design an accurate model and simulate strategies on it. Two strategies are involved: feed-forward control with an accelerometer placed on the mobile mass for acceleration detection and the second one is based on movement detection using the self-induced current due to the actuator's coil movement in a magnetic field. A detailed simulation model, using a software designed for electronic circuit simulation and experimental testing are performed in both cases. The model should be improved for considering the complex impedance of the actuator (mechanically but also electrically), this being the subject of future works.